2012
DOI: 10.1177/0192636512459554
|View full text |Cite
|
Sign up to set email alerts
|

School Leaders’ Perceptions About Incompetent Teachers

Abstract: This study explored Wyoming school leaders’ perceptions about the traits of incompetent teachers, strategies used to work with incompetent teachers, and the barriers to their dismissal. Most importantly, this study differentiated how principals and superintendents viewed incompetency issues. Some major findings include school leaders’ beliefs that classroom management problems were an indicator of incompetence, counseling to leave the profession was a strategy used with incompetent teachers, and teacher unions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(37 citation statements)
references
References 40 publications
4
31
0
2
Order By: Relevance
“…Public schools are being examined, and the people they serve are calling for improvement (Tucker & Stronge, 2005). One area that can be agreed upon is the importance of teacher quality in improvement efforts (Corcoran, 2007;McQuarrie & Wood, 1991;Owings, Kaplan, Nunnery, Marzano, Myran, & Blackburn, 2006;Range, Duncan, Scherz, & Haines, 2012).…”
Section: )mentioning
confidence: 99%
See 4 more Smart Citations
“…Public schools are being examined, and the people they serve are calling for improvement (Tucker & Stronge, 2005). One area that can be agreed upon is the importance of teacher quality in improvement efforts (Corcoran, 2007;McQuarrie & Wood, 1991;Owings, Kaplan, Nunnery, Marzano, Myran, & Blackburn, 2006;Range, Duncan, Scherz, & Haines, 2012).…”
Section: )mentioning
confidence: 99%
“…Research has shown evidence that the quality of teachers has decreased steadily over time, while nearly all modern research claims teacher effectiveness to be among the most effective strategy schools have to improve student achievement (Corcoran, 2007;McQuarrie & Wood, 1991;Owings et al, 2006;Range et al, 2012). Goe (2007) also supported this stance by stating that teacher quality matters a great deal in regard to student learning.…”
Section: Teacher Effects On Student Learningmentioning
confidence: 99%
See 3 more Smart Citations